Psychiatric Morbidities among Attenders of an Islamic Spiritual Healing Centre in Malaysia - Abdullah, KHA; Saini, SM; Sharip, S; Shaharom, MH (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by SCOPUS